Big Data Analytics: Transforming Business Intelligence and Decision Making - Wendi Usino; Dhiyah Ayu Rini Kusumawardhani; Tarisya Ramadhan; Aptanta Pratiangga; Olivia Qurotulain (Pandawan Sejahtera Indonesia, 2024)
In today's rapidly evolving digital landscape, organizations are increasingly leveraging Big Data Analytics to transform business intelligence and enhance decision-making processes. This study explores how businesses utilize Big Data to gain insights into operations, customer behaviors, and market trends, specifically focusing on the retail, healthcare, and financial sectors. By employing a mixed-method approach that combines qualitative and quantitative data, the research analyzes case studies from a major international retailer, a leading healthcare provider, and a global bank. Data sources include semi-structured interviews with industry experts, surveys, and secondary data from existing literature. The findings indicate significant improvements in customer retention (20%), operational efficiency (with a 15% reduction in inventory costs in retail and a 10% reduction in hospitalization rates in healthcare), and fraud reduction (a 25% decrease in fraudulent transactions in financial services). However, the study also identifies ongoing challenges such as data quality issues, high implementation costs, and complexities in integrating Big Data Analytics with existing systems. The research concludes by emphasizing the importance of addressing these challenges to fully capitalize on Big Data's potential for competitive advantage and suggests that future studies should explore the ethical implications and the impact of emerging technologies on Big Data Analytics to further enhance its effectiveness in business intelligence.